Cell-based therapy in prophylaxis and treatment of chronic graft-versus-host disease - Doglio, Matteo; Crossland, Rachel E.; Alho, Ana C.; Penack, Olaf; Dickinson, Anne M.; Stary, Georg; Lacerda, João F.; Eissner, Günther; Inngjerdingen, Marit (Frontiers in Immunology, 2022)
Hematopoietic allogeneic stem cell transplantation (allo-SCT) is a curative option for patients with hematological malignancies. However, due to disparities in major and minor histocompatibility antigens between donor and recipient, severe inflammatory complications can occur, among which chronic graft-versus-host disease (cGVHD) can be life-threatening. A classical therapeutic approach to the prevention and treatment of cGVHD has been broad immunosuppression, but more recently adjuvant immunotherapies have been tested. This review summarizes and discusses immunomodulatory approaches with T cells, including chimeric antigen receptor (CAR) and regulatory T cells, with natural killer (NK) cells and innate lymphoid cells (ILCs), and finally with mesenchymal stromal cells (MSC) and extracellular vesicles thereof. Clinical studies and pre-clinical research results are presented likewise.